The Cost Effectiveness of Ecotherapy as a Healthcare Intervention, Separating the Wood from the Trees - Sebastian Hinde (MDPI AG, 2021)
Internationally, shifts to more urbanised populations, and resultant reductions in engagements with nature, have been a contributing factor to the mental health crisis facing many developed and developing countries. While the COVID-19 pandemic reinforced recent trends in many countries to give access to green spaces more weight in political decision making, nature-based activities as a form of intervention for those with mental health problems constitute a very small part of patient pathways of care. Nature-based interventions, such as ecotherapy, are increasingly used as therapeutic solutions for people with common mental health problems. However, there is little data about the potential costs and benefits of ecotherapy, making it difficult to offer robust assessments of its cost-effectiveness. This paper explores the capacity for ecotherapy to be cost-effective as a healthcare intervention. Using a pragmatic scoping review of the literature to understand where the potential costs and health benefit lie, we applied value of information methodology to identify what research is needed to inform future cost-effectiveness assessments. We show that there is the potential for ecotherapy for people with mild to moderate common mental health problems to be cost-effective but significant further research is required. Furthermore, nature-based interventions such as ecotherapy also confer potential social and wider returns on investment, strengthening the case for further research to better inform robust commissioning.